2018
DOI: 10.1128/jvi.00146-18
|View full text |Cite
|
Sign up to set email alerts
|

A Polyamide Inhibits Replication of Vesicular Stomatitis Virus by Targeting RNA in the Nucleocapsid

Abstract: Polyamides have been shown to bind double-stranded DNA by complementing the curvature of the minor groove and forming various hydrogen bonds with DNA. Several polyamide molecules have been found to have potent antiviral activities against papillomavirus, a double-stranded DNA virus. By analogy, we reason that polyamides may also interact with the structured RNA bound in the nucleocapsid of a negative-strand RNA virus. Vesicular stomatitis virus (VSV) was selected as a prototype virus to test this possibility s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(78 reference statements)
2
6
0
Order By: Relevance
“…Both of these experiments depict a large stabilization of the NLP by poly(rA). This is consistent with data from a previous study in which a polyamide (UMSL1011) that stabilizes the RNA in NLPs delayed RNA thermo-release by 2.04°C (24). These experimental results confirmed that nucleocapsid stability is dependent on the purine content of sequestered RNA, which may change the accessibility of the genomic RNA in the nucleocapsid to vRdRp to modulate its transcription/replication activities.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Both of these experiments depict a large stabilization of the NLP by poly(rA). This is consistent with data from a previous study in which a polyamide (UMSL1011) that stabilizes the RNA in NLPs delayed RNA thermo-release by 2.04°C (24). These experimental results confirmed that nucleocapsid stability is dependent on the purine content of sequestered RNA, which may change the accessibility of the genomic RNA in the nucleocapsid to vRdRp to modulate its transcription/replication activities.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that the incorporation of poly(rA) in the NLP increased the stability by 2.33°C compared to the recombinantly purified NLP with a random RNA sequence (20) and by 2.96°C compared to the NLP with poly(rU). Furthermore, incorporation of poly(rA) in the NLP delayed the thermorelease of RNA by 7.86°C compared to the recombinantly purified NLP with a random RNA sequence and by 8.81°C compared to the NLP with poly(rU) (24). Both of these experiments depict a large stabilization of the NLP by poly(rA).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…By thermal shift assays of nucleocapsid stability, it was shown that a nucleocapsid-like particle (NLP) containing poly(rA) is more stable than that containing random RNA sequences [67]. This is consistent with the observation that a compound stabilizing the nucleocapsid also inhibits viral RNA synthesis by VSV polymerase [68]. On the other hand, an NLP containing poly(rU) is less stable than that containing random RNA sequences, suggesting polymerase stuttering may be related to instability of the nucleocapsid.…”
Section: Viral Rna Synthesissupporting
confidence: 68%